2004
DOI: 10.1111/j.1365-2222.2004.01854.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of glucocorticoid and cysteinyl leukotriene receptor antagonist treatments in an experimental model of chronic airway inflammation in guinea‐pigs

Abstract: Although leukotriene receptor antagonist treatment reduces eosinophil accumulation induced by multiple antigen challenges, glucocorticoid treatment attenuates both eosinophil and mononuclear cell infiltration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0
39

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(96 citation statements)
references
References 48 publications
6
51
0
39
Order By: Relevance
“…In addition, we have previously shown (28) that chronic L-NAME treatment in this animal model reduced the exhaled NO by ϳ50% compared with controls. The L-NAME treatment began 24 h after the forth inhalation to avoid interference with the sensitization since in this period animals have already been sensitized (IgG 1 title 1:320) (16). In fact we had previously evaluated the effects of this approach of L-NAME treatment in the sensitization process, and we observed that this treatment did not interfere with the sensitization (26,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have previously shown (28) that chronic L-NAME treatment in this animal model reduced the exhaled NO by ϳ50% compared with controls. The L-NAME treatment began 24 h after the forth inhalation to avoid interference with the sensitization since in this period animals have already been sensitized (IgG 1 title 1:320) (16). In fact we had previously evaluated the effects of this approach of L-NAME treatment in the sensitization process, and we observed that this treatment did not interfere with the sensitization (26,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…20). Excess NO has been correlated with the degree of airway inflammation in asthma patients and animal models (27,32,39,50,51,56). Although the role of elevated NO in asthma is accepted, the relative contribution of each of the NOS isoforms to the production of NO in asthma is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Among downstream lipid mediators of 5-lipoxygenase, cysteinyl LTs (LTC 4 , D 4 , and E 4 ), originally termed slow-reacting substance of anaphylaxis have been reported to increase vascular permeability, and bronchial smooth muscle constriction, through two distinct types of receptors, CysLT1 and CysLT2. Although several CysLT1 antagonists such as zafirlukast, montelukast, and pranlukast are currently used for treatment of asthmatic patients, the effect is heterogeneous, and a significant number of patients are resistant to the CysLT antagonist treatment (16). Leukotriene B 4 (LTB 4 ), another eicosanoid derived from 5-lipoxygenase pathway of arachidonic acid, has well-documented potent chemotactic activity toward granulocytes (17).…”
mentioning
confidence: 99%